Emissions, trade openness, urbanisation, and income in Thailand: An empirical analysis - Rossarin Osathanunkul (2018)
© Springer International Publishing AG 2018. This study investigates the relationship between emissions, income, energy consumption, trade openness, and urbanisation in Thailand over the period of 1971 to 2014. The ARDL cointegration technique is employed and CUSUM and CUSUMSQ tests are used to ensure the stability of the estimated results. Our findings indicate there is a long run relationship among variables for the case of CO 2 emissions while there is none for the SO 2 . The results indicate an increase in income can cause significantly more CO 2 emissions. Energy consumption also contributes to environmental degradation with slight impact, while there is no effect from trade openness. On the contrary, urbanisation greatly helps reduce CO 2 emissions in the long run.